No safe renal warm ischemia time—The molecular network characteristics and pathological features of mild to severe ischemia reperfusion kidney injury - Chen, Ya-Lei; Li, Huai-Kang; Wang, Lei; Chen, Jian-Wen; Ma, Xin (Frontiers in Molecular Biosciences, 2022)
Ischemic Acute kidney injury (AKI) has always been a hot and difficult research topic in the field of renal diseases. This study aims to illustrate the safe warm ischemia time of kidney and the molecular network characteristics and pathological features of mild to severe ischemia reperfusion kidney injury. We established an ischemia time set every 2 minutes on a relatively stable ischemia-reperfusion injury (IRI) model with unilateral ischemia (left kidney) and contralateral (right kidney) resection (uIRIx) to establish varying degrees of renal injury, our results indicated that there was no absolute safe renal warm ischemia time, and every minute of ischemia increases kidney damage. Warm ischemia 26min or above in mice makes severe kidney injury, renal pathology and serum creatinine (SCr) were significantly changed. Warm ischemia between 18 and 26 minutes makes mild kidney injury, with changes in pathology and renal molecular expression, while SCr did not changed. No obvious pathological changes under 16min warm ischemia, while significant differences were found in molecular expression. There are two key time intervals in the process of renal ischemia injury, 0min to 16min and 26min to 28min. Gene expression of immune-related pathways were most significantly down-regulated in short-term ischemia, while metabolism-related pathways were the mainly enriched pathway in long-term ischemia. Taken together, this study provides novel insights into safe renal artery occlusion time in partial nephrectomy, and is of great value for elucidating molecular network characteristics and pathological features of mild to severe ischemia reperfusion kidney injury, and key genes related to metabolism and immune found in this study also provide potential diagnostic and therapeutic biomarkers for AKI.